An Economic Analysis of Crop Yield and Product Price Variability in Bijapur Arid Agriculture, Karnataka - Mruthyunjaya, Mruthyunjaya; Sirohi, A S (Annals of Arid Zone, 2016)
Bijapur district in Karnataka State is a typical drought prone tract. The nature and magnitude of crop yield and product price variability in this tract is investigated in this paper by examining the coefficient of variation of crop yields, product prices etc. Some of the important findings of the study are: i) crop yield instability was the highest in case of oil seed crops, followed by pulses, cereals and cotton; ii) continuance of poor crop conditions for successive four and above years was overwhelming in the study area; iii) low yield of a crop was accompanied by low yeild of one or more of the remaining crops too; iv) with jowar crop as an exception, instability of product prices was dominant over that of crop yields; and v) there was high covariance between product prices. Creation of irrigation facilities, opening grain and fodder banks, creating a net work of motorable roads are suggested for development of these areas.